Bitcoin and Vietnam Stock Markets: Evidence from COVID-19 and Russia-Ukraine Crises - Ngo Thai , Hung; Nguyen Minh Da , Man; The Thi Hoai , Ngoc; Pham Thi , Ngoc; Tran Thi Minh , Phuong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study aims to explore the return spillover effects between Bitcoin and stock markets in Vietnam during the COVID-19 and Russia-Ukraine crises. By doing so, the authors employ the DECO-GARCH model and spillover index proposed by Diebold and Yilmaz (2014). Empirical analysis uncovers that there exists a time-varying equicorrelation between Bitcoin and stock market returns during the sample period. In addition, the price spillover effects between Bitcoin and Vietnam stock markets have a high level of 48%, which implies that there is a significant connectedness between these time series. These results have important implications for investors and market participants.
Keywords: DECO-GARCH; Bitcoin; Stock Markets; Vietnam; COVID–19; Russia-Ukraine